2019
DOI: 10.11646/zootaxa.4674.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Amerila (Lepidoptera: Erebidae: Arctiinae) of Cameroon with morphological remarks on male and female genitalia

Abstract: Amerila is one of the most studied Afrotropical genera of Arctiinae. However, based on a regionally constrained sample of specimens from Mount Cameroon, we show how superficial our knowledge on these tiger moths is. Among six collected Amerila species, A. femina’s female is described here for the first time, and A. mulleri and A. roseomarginata had never been recorded before in the country. Moreover, novel biological data are presented, including individual species’ elevational ranges. Finally, female reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 818 publications
(6 citation statements)
references
References 15 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Mount Cameroon is known to harbour high diversity in many taxa, including other Lepidoptera groups (e.g., Ballesteros-Mejia et al 2013 ; Maicher et al 2016 ; Przybyłowicz et al 2019 ; Delabye et al 2020 , Mertens et al 2021 ). The region’s exceptional species richness is often attributed to its location at the confluence of the Guinean and Congolian biogeographic regions, and a presence of diverse habitats along its elevational and precipitation gradients ( Cable and Cheek 1998 ; Bergl et al 2007 ; Hořák et al 2019 ; Maicher et al 2020a ; Delabye et al 2021 ; Doležal et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mount Cameroon is known to harbour high diversity in many taxa, including other Lepidoptera groups (e.g., Ballesteros-Mejia et al 2013 ; Maicher et al 2016 ; Przybyłowicz et al 2019 ; Delabye et al 2020 , Mertens et al 2021 ). The region’s exceptional species richness is often attributed to its location at the confluence of the Guinean and Congolian biogeographic regions, and a presence of diverse habitats along its elevational and precipitation gradients ( Cable and Cheek 1998 ; Bergl et al 2007 ; Hořák et al 2019 ; Maicher et al 2020a ; Delabye et al 2021 ; Doležal et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amerila mulleri was described from the Vumba Mountains in Zimbabwe and reported from Ituri in North Kivu (DRC), the Kakamega Forest in Kenya and Swaziland (Häuser & Boppré 1997). The species has later been recorded from the Mount Cameroon (Przybyłowicz et al 2019b) representing a population being geographically rather remote from the East African main range. Amerila francesae seems to have a more limited distribution with scattered records from the Eastern Arc Mountains in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expect that most of this many-plumed moth diversity is endemic to the study area. Several other potentially endemic species of moths (e.g., Yakovlev and Sáfián 2016;De Prins and De Prins 2019;Przybyłowicz et al 2019;) and butterflies (e.g., Larsen 2005;Sáfián and Tropek, 2016;Sáfián et al 2019) are already known from Mount Cameroon. Nevertheless, the real character of the endemism within Alucitidae on Mount Cameroon, as well as the mechanisms underlying the group's speciation (or even local radiation), will need more detailed research.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in Ustjuzhanin et al (2018), Alucitidae are strongly understudied in the Afrotropics. While several recent faunistic (Maicher et al 2016;Przybyłowicz et al 2019;Delabye et al 2020) and taxonomic (Przybyłowicz 2013;Sáfián and Tropek 2016;Yakovlev and Sáfián 2016;Sáfián et al 2019) discoveries have shown the Mount Cameroon region as an important but largely understudied locality for lepidopteran biodiversity, its importance for Alucitidae biodiversity in particular remains unrivalled. Of 70 Afrotropical species of many-plumed moths, 32 are known from the Guineo-Congolian forest zone (De Prins and De Prins 2019); 15 of these have been already described or reported from Mount Cameroon (Ustjuzhanin et al 2018).…”
Section: Introductionmentioning
confidence: 99%